Lymphatic Expression of CLEVER-1 in Breast Cancer and Its Relationship with Lymph Node Metastasis. (2011) - Ammar, Aula; Mohammed, Rabab A. A.; Salmi, Marko; Pepper, Michael; Paish, Emma C.; Ellis, Ian O.; Martin, Stewart G.
Abstract : Background : Mechanisms regulating breast cancer lymph node metastasis are unclear. Staining of CLEVER-1 (common lymphatic endothelial and vascular endothelial receptor-1) in human breast tumors was used, along with in vitro techniques, to assess involvement in the metastatic process. Methods : 148 sections of primary invasive breast cancers, with 10 yr follow-up, were stained with anti-CLEVER-1. Leukocyte infiltration was assessed, along with involvement of specific subpopulations by staining with CD83 (mature dendritic cells, mDC), CD209 (immature DC, iDC) and CD68 (macrophage, M&phis;). in vitro expression of CLEVER-1 on lymphatic (LEC) and blood endothelial cells (BEC) was examined by flow cytometry. Results : in vitro results showed that although both endothelial cell types express CLEVER-1, surface expression was only evident on LEC. In tumour sections CLEVER-1 was expressed in blood vessels (BV, 61.4% of samples), lymphatic vessels (LV, 18.2% of samples) and in M&phis;/DCs (82.4% of samples). However, only CLEVER-1 expression in LV was associated with LN metastasis ( p = 0.027) and with M&phis; indices ( p = 0.021). Although LV CLEVER-1 was associated with LN positivity there was no significant correlation with recurrence or overall survival, BV CLEVER-1 expression was, however, associated with increased risk of recurrence ( p = 0.049). The density of inflammatory infiltrate correlated with CLEVER-1 expression in BV (p < 0.001) and LV ( p = 0.004). Conclusions : The associations between CLEVER-1 expression on endothelial vessels and macrophage/leukocyte infiltration is suggestive of its regulation by inflammatory conditions in breast cancer, most likely by macrophage-associated cytokines. Its upregulation on LV, related surface expression, and association with LN metastasis suggest that it may be an important mediator of tumor cell metastasis to LN.